Laparoscopy in infants and children - Zachariou, Zacharias; Ure, B. (Berlin, Gw. : Springer-Verlag, 2004)
(Producer) Offers detailed information on the most common laparoscopic procedures. Presented in a multimedia format, including text, sound, full screen or videos, and narration, delineating the clinical problem with practical information on the preoperative workup, the patient and trocar position, the operation, postoperative care and possible complications
System requirements: Pentium with 266 MHz; 32 MB RAM; Windows 98, ME, NT 4.0, 2000, XP; Hi-Color-Video Card; resolution 800x600; DVD-drive; sd. card.
Keywords: Laparoscopy -- child; Laparoscopy -- infant